2019
DOI: 10.1371/journal.pone.0214100
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of non-invasive low intensity pulsed electric field and fucoidan in preventing oxidative stress-induced motor neuron death via ROCK/Akt pathway

Abstract: With the expansion of the aged population, it is predicted that neurodegenerative diseases (NDDs) will become a major threat to public health worldwide. However, existing therapies can control the symptoms of the diseases at best, rather than offering a fundamental cure. As for the complex pathogenesis, clinical and preclinical researches have indicated that oxidative stress, a central role in neuronal degeneration, is a possible therapeutic target in the development of novel remedies. In this study, the motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…Treatment of SH-SY5Y cells with 500 μM H 2 O 2 for 24 h reduced the cell viability to 52% compared to the control cells, which was used in the subsequent experiments. To examine whether H-LIPEF could produce protection and increase the cell viability against the oxidative insult, cells were pretreated with H-LIPEF for 4 h and then exposed to H 2 O 2 in the continuous administration of H-LIPEF for another 24 h. In our previous study, the low frequency LIPEF with parameters of 2 Hz, 60V/cm, and 2 ms pulse duration was used in the mouse motor neurons NSC-34 [ 12 ], but the result showed that this parameter combination is ineffective in the SH-SY5Y cells. In this study, we used H-LIPEF in our experiments, and found that the H-LIPEF stimulation using the parameters of 200 Hz, 10 V/cm, and 2 ms pulse duration produced significant protection against the oxidative insult caused by H 2 O 2 to SH-SY5Y human neural cell line.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of SH-SY5Y cells with 500 μM H 2 O 2 for 24 h reduced the cell viability to 52% compared to the control cells, which was used in the subsequent experiments. To examine whether H-LIPEF could produce protection and increase the cell viability against the oxidative insult, cells were pretreated with H-LIPEF for 4 h and then exposed to H 2 O 2 in the continuous administration of H-LIPEF for another 24 h. In our previous study, the low frequency LIPEF with parameters of 2 Hz, 60V/cm, and 2 ms pulse duration was used in the mouse motor neurons NSC-34 [ 12 ], but the result showed that this parameter combination is ineffective in the SH-SY5Y cells. In this study, we used H-LIPEF in our experiments, and found that the H-LIPEF stimulation using the parameters of 200 Hz, 10 V/cm, and 2 ms pulse duration produced significant protection against the oxidative insult caused by H 2 O 2 to SH-SY5Y human neural cell line.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, non-invasive low-intensity pulsed electric field (LIPEF) was employed, in conjunction with fucoidan, in preventing oxidative stress-induced mouse motor neuron death [ 12 ]. It found that LIPEF suppressed the hydrogen peroxide (H 2 O 2 )-enhanced expression of ROCK protein and increased the phosphorylation of Akt in H 2 O 2 -treated NSC-34 cell line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of SH-SY5Y cells with 500 µM H 2 O 2 for 24 h reduced the cell viability to 52% compared to the control cells, which was used in the subsequent experiments. To examine whether H-LIPEF could produce protection and increase the cell viability against the oxidative insult, cells were pretreated with H-LIPEF for 4 h and then exposed to H 2 O 2 in the continuous administration of H-LIPEF for another 24 h. In our previous study, the low frequency LIPEF with parameters of 2 Hz, 60V/cm, and 2 ms pulse duration was used in the mouse motor neurons NSC-34 [12], but the result showed that this parameter combination is ineffective in the SH-SY5Y cells. In this study, we used H-LIPEF in our experiments, and found that the H-LIPEF stimulation using the parameters of 200 Hz, 10 V/cm, and 2 ms pulse duration produced significant protection against the oxidative insult caused by H 2 O 2 to SH-SY5Y human neural cell line.…”
Section: Resultsmentioning
confidence: 99%
“…The method of such non-invasive strategy of LIPEF is somewhat similar to that of tumor treating fields [19], but in a non-contact approach with different waveform and field strength. Furthermore, exposure to non-invasive LIPEF can be viewed as the simultaneous interaction of multiple frequencies [20] with a biological sample due to the electrical dispersion caused by the encounter with biological dielectrics.…”
Section: Experimental Setup Of Lipefmentioning
confidence: 99%